Rice DST transcription factor negatively regulates heat tolerance through ROS-mediated stomatal movement and heat-responsive gene expression - Ding, Yanfei; Zhou, Mei; Wang, Ke; Qu, Aili; Hu, Shanshan; Jiang, Qiong; Yi, Keke; Wang, Feijuan; Cai, Chong; Zhu, Cheng; Chen, Zhixiang (Frontiers in Plant Science, 2023)
Plants are frequently subjected to a broad spectrum of abiotic stresses including drought, salinity and extreme temperatures and have evolved both common and stress-specific responses to promote fitness and survival. Understanding the components and mechanisms that underlie both common and stress-specific responses can enable development of crop plants tolerant to different stresses. Here, we report a rice heat stress-tolerant 1 (hst1) mutant with increased heat tolerance. HST1 encodes the DST transcription factor, which also regulates drought and salinity tolerance. Increased heat tolerance of hst1 was associated with suppressed expression of reactive oxygen species (ROS)-scavenging peroxidases and increased ROS levels, which reduced water loss by decreasing stomatal aperture under heat stress. In addition, increased ROS levels enhanced expression of genes encoding heat shock protein (HSPs) including HSP80, HSP74, HSP58 and small HSPs. HSPs promote stabilization of proteins and protein refolding under heat stress and accordingly mutation of HST1 also improved reproductive traits including pollen viability and seed setting under high temperature. These results broaden the negative roles of DST in abiotic stress tolerance and provide important new insights into DST-regulated tolerance to diverse abiotic stresses through both shared and stress-specific mechanisms.